Maternal infection and the offspring brain - Depino, Amaicha Mara (2006)
Fil: Depino, Amaicha Mara. European Molecular Biology Laboratory. Mouse Biology Unit; Italia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Investigaciones Bioquímicas de Buenos Aires. Fundación Instituto Leloir. Instituto de Investigaciones Bioquímicas de Buenos Aires; Argentina